Recent Advances in Analytical Chemistry - Ince, Muharrem; Kaplan Ince, Olcay (IntechOpen, 2019)
This book focuses on recent and future trends in analytical methods and provides an overview of analytical chemistry. As a comprehensive analytical chemistry book, it takes a broad view of the subject and integrates a wide variety of approaches. The book provides separation approaches and method validation, as well as recent developments and applications in analytical chemistry. It is written primarily for researchers in the fields of analytical chemistry, environmental chemistry, and applied chemistry. The aim of the book is to explain the subject, clarify important studies, and compare and develop new and groundbreaking applications. Written by leading experts in their respective areas, the book is highly recommended for professionals interested in analytical chemistry because it provides specific and comprehensive examples.